THE IMPLEMENTATION OF TOTAL PHYSICAL RESPONSE IN TEACHING WRITING THE PROCEDURAL TEXT - Silmi, Rifka (2017)
This study is focused on the implementation of Total Physical Response in teaching writing of procedural text in one public school in Bandung. This study intended to explore how total physical response was conducted in the classroom to help students write procedure text. To meet the purpose, this study employed a descriptive qualitative research design embracing the characteristics of a case study approach. The main data were from the observation sheet and the results of students' interviews and questionnaire. All the data were analysed to explore how Total Physical Response conducted in the classroom. The analysis of the study revealed that Total Physical Response was helpful to students in learning writing of procedural text. Total Physical Response helped the students in recalling the words and the general structure of procedural text. The students were also able to communicate with each other confidently. The students' procedure texts were found to be more structured and coherent. Based on the findings, it is recommended that Total Physical Response is able to used in teaching writing of procedural text, particularly in helping the students to recall the words quickly and to write the text structurally.---------- Penelitian ini fokus pada implementasi Total Physical Response untuk pembelajaran menulis teks prosedur di salah satu sekolah di Bandung. Penelitian ini bertujuan untuk menyelidiki bagaimana total physical response yang dilaksanakan di kelas dapat membantu siswa dalam menulis teks prosedur. Untuk mencapai tujuan tersebut, penelitian in menerapkan desain penelitian deskriptif kualitatif dengan karakteristik studi kasus. Data utama penelitian ini berasal dari lembar observasi dan hasil wawancara dan daftar pertanyaan/angket. Semua data dianalisis untuk menyelidiki bagaimana Total Physical Response yang dilaksanakan di kelas dapan membantu siswa dalam menulis teks prosedur. Penelitian ini mengungkapkan bahwa Total Physical Response dapat membantu siswa dalam belajar menulis teks prosedur. Total Physical Response membantu siswa dalam mengingat kata dan strukstur teks prosedur. Siswa juga dapat berkomunikasi satu sama lain dengan percaya diri. Teks-teks siswa terlihat lebih terstruktur dan koheren. Berdasarkan hasil penelitian, direkomendasikan agar penelitian menggunakan Total Physical Response dapat diterapkan dalam pengajaran menulis teks prosedur, khususnya dalam membantu siswa dalam mengingat kata dengan cepat dan menulis teks dengan terstruktur.